The Sehgal’s Fixed Point Result in the Framework of ρ-Space - Nicolae Adrian Secelean; Dariusz Wardowski; Mi Zhou (Mathematics, 2022)
In this paper, we prove a fixed point theorem of Sehgal type (see Sehgal, V.M., Proc Amer Math Soc 23: 631–634, 1969) in a more general setting of <semantics>ρ</semantics>-space (see Secelean, N.A. and Wardowski, D., Results Math, 72: 919–935, 2017). In this way, we can find, as particular cases, some results of Sehgal type in metric, b-metric and rectangular b-metric spaces.